Global Trends and Performances of Magnetic Resonance Imaging Studies on Acupuncture: A Bibliometric Analysis - Zhang, Jinhuan; Zhang, Yangxin; Hu, Liyu; Huang, Xingxian; Liu, Yongfeng; Li, Jiaying; Hu, Qingmao; Xu, Jinping; Yu, Haibo (Frontiers in Neuroscience, 2021)
Objectives: To summarize development processes and research hotspots of MRI researches on acupuncture and to provide new insights for researchers in future studies. Methods: Publications regarding MRI on acupuncture from inception to 2020 were downloaded from the Web of Science Core Collection. VOSviewer 1.6.15 and CiteSpace V software were used for bibliometric analyses. The main analyses include collaboration analyses between countries / institutions / authors, co-occurrence analysis between keywords, as well as analyses on keyword burst, citation reference and clusters of references. Results: A total of 829 papers were obtained with a continually increased trend over time. The most productive country/region and institution in this field was the People’s Republic of China (475) and KyungHee University (70), respectively. Evidence-based Complementary and Alternative Medicine (83) was the most productive journal, and Neuroimage (454) was the most co-cited journal. Rupali P Dhond’s (2008) article (co-citation counts: 58) and the Vitaly Napadow’s (2005) article (centrality: 0.21) were the most representative and symbolic references, with the highest co-citation number and centrality, respectively. Jie Tian has the highest number of publications (35) and Kathleen K S Hui was the most influential author (280 co-citations). The four hot topics in MRI on acupuncture were acupuncture, fMRI, pain, and stimulation. The three frontier topics were connectivity, modulation and fMRI. Based on the clustering of co-cited documents, chronic low back pain, sham electro-acupuncture treatment, clinical research were the main research direction. Conclusion: This study provides an in-depth perspective for MRI research on acupuncture, and provides researchers with valuable information to determine the current status, hot spots and frontier trends of MRI research on acupuncture.